2019
DOI: 10.3390/su11164414
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Indirect Carbon Emission of Residential Consumption in China: A Case of Liaoning Province

Abstract: Indirect carbon emissions caused by residential consumption has gradually become the key to the formulation of carbon emission reduction policies. In order to analyze the factors that influence the provincial residential indirect carbon emissions in China, comprehensive structural decomposition analysis (SDA) and logarithmic mean Divisia index (LMDI) models are established in this paper. The Liaoning province was selected due to its typical features as a province with higher urbanization rates. The model is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Within cities, buildings consume 36% of energy and produce 40% of emissions [4], with electricity and natural gas being the usual forms of consumption in them [5]. Furthermore, they are responsible for the main growth in emissions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Within cities, buildings consume 36% of energy and produce 40% of emissions [4], with electricity and natural gas being the usual forms of consumption in them [5]. Furthermore, they are responsible for the main growth in emissions [6].…”
Section: Introductionmentioning
confidence: 99%
“…While those of indirect origin are a consequence of the purchase and use of products and services by consumers to satisfy their basic needs. These residential emissions are those that cause the greatest growth in direct and indirect CO 2 emissions [49]. Thus, these two types of emissions represent more than 40% of carbon emissions in China [50], while estimates for the USA reach 80% [51].…”
Section: Direct and Indirect Residential Emissionsmentioning
confidence: 99%
“…Some scholars indicated that the consumption of urban residents was the most significant factor leading to the increase of direct and indirect carbon emissions, and both showed a significant upward trend [34,35]. The carbon consumption of Chinese residents (rural and urban) grew steadily.…”
Section: The Impact Of Resident Consumption and Employment Structure mentioning
confidence: 99%